HEGEMONI AGAMA DI INDONESIA: PERSPEKTIF PASTORAL LINTAS AGAMA - Rynaldi Mahardika Situmeang (Bethel Press, 2024)
This article aims to examine the religious hegemony that is currently occurring in Indonesia, where in several cases that have occurred over the last five years, the dominance of one religion over another religion is clear and occurs continuously. This can certainly damage the perfection of diversity in Indonesia itself, considering that diversity is one of the characteristics inherent in Indonesia's identity as a great nation. Religious hegemony in Indonesia is considered the